Stalking behaviors among perpetrators of intimate partner violence in Portugal: correlates and mediating variables - Cunha, Olga Cecília Soares (2022)
Intimate partner violence (IPV) and intimate partner stalking (IPS) frequently co-occur. However, the relationship between IPV and IPS has raised different interpretations: some researchers defend that they are similar types of crime, and others suggest that IPS is an extension of IPV. Using a sample of 284 male perpetrators from Portugal, recruited from prison and community, in this study, we intended to compare IPV perpetrators with and without IPS behaviors, identify the factors that predict IPS, and explore the mediating effects of the prediction variables on IPS. Results revealed that although similar in some features (e.g., psychopathology, aggression, previous convictions), IPV perpetrators with IPS differentiate from IPV perpetrators without IPS in drug abuse, separation from the victim, frequency of IPV, frequency of psychological IPV, psychopathy, and psychopathy lifestyle facet. However, only the separation from the victim, IPV frequency, and intimate psychological violence frequency predicted IPS. The mediation analyses showed that separation alone does not explain stalking behaviors and that IPV frequency plays an important mediating role. Our study reinforces the link and even the continuum nature between IPV and IPS. Thus, stalking behaviors should be considered in prevention and intervention efforts in this area